Математические модели дискретного канала связи - Горбачёв, Виктор Васильевич; Гарных, В. И. (НТУ "ХПИ", 2008)
В статті розглянуто математичні моделі дискретного каналу зв’язку. Було показано, що найбільш відпрацьованою в плані створення математичного апарату для розв’язання завдань аналізу показників якості передачі дискретної інформації є марківські моделі.

Mathematical models of the discrete channel relationship are considered in article. There was is shown, the studied carefullied in plan of the making the mathematical device for decision of the problems of the analysis of the factors quality issues to discrete information are Markov’s models.
Keywords: цепь Маркова; ошибка; экспериментальные данные; данные; марковская модель